Collaborative care model for diabetes in primary care settings in Qatar: a qualitative exploration among healthcare professionals and patients who experienced the service - Sara Abdulrhim; Sowndramalingam Sankaralingam; Mohamed Izham Mohamed Ibrahim; Mohammed Issam Diab; Mohamed Abdelazim Mohamed Hussain; Hend Al Raey; Mohammed Thahir Ismail; Ahmed Awaisu (BMC, 2021)
Abstract Background Diabetes mellitus is highly prevalent and associated with huge economic burden globally. The conventional care and management of diabetes mellitus is highly fragmented and complex, warranting the need for a comprehensive Collaborative Care Model (CCM). Little is known about the perception of patients with diabetes and their healthcare providers about CCM, its barriers and facilitators. This study aimed to explore the value of CCM in diabetes care at a primary healthcare (PHC) setting from the perspective of patients with diabetes and healthcare professionals (HCPs), in an effort to expand our current knowledge on collaborative care in diabetes at primary care level for the purpose of quality improvement and service expansion. Methods Using an exploratory case study approach, semi-structured interviews were conducted among patients and HCPs who encountered CCM in Qatar during 2019 and 2020. The semi-structured interviews were transcribed verbatim and the data were analysed and interpreted using a deductive-inductive thematic analysis approach. Results Twelve patients and 12 HCPs at a diabetes clinic participated in one-to-one interviews. The interviews resulted in five different themes: the process and components of collaborative care model (four subthemes), current organizational support and resources (three subthemes), impact of collaborative care model on diabetes outcomes (three subthemes), enablers of collaborative care model (three subthemes), and barriers to collaborative care model (three subthemes). The participants indicated easy access to and communication with competent and pleasant HCPs. The patients appreciated the extra time spent with HCPs, frequent follow-up visits, and health education, which empowered them to self-manage diabetes. HCPs believed that successful CCM provision relied on their interest and commitment to care for patients with diabetes. Generally, participants identified barriers and facilitators that are related to patients, HCPs, and healthcare system. Conclusions The providers and users of CCM had an overall positive perception and appreciation of this model in PHC settings. Barriers to CCM such as undesirable attributes of HCPs and patients, unsupportive hospital system, and high workload must be addressed before implementing the model in other PHC settings.